United Republic of Tanzania Public Expenditure Review FY03 : Managing Public Expenditures for Poverty Reduction - Report on Fiscal Developments and Public Expenditure Management Issues - World Bank (Washington, DC, 2013)
In line with the Poverty Reduction Strategy (PRS) context, this external evaluation looks at budgetary developments, primarily through the lens of the PRS, thus with important implications for the Public Expenditure Review (PER) process, which has evolved into the principal analytic instrument to support the translation of PRS objectives and strategies, into budgets. Overall fiscal policy remained very conservative in FY02, and FY03. Tanzania continues to use a cash budget system that strictly constrains spending, and commitment levels to short term availability of cash. While the system was clearly useful, improvements in budget and aid management put the continued use of a cash budget system into question; thus it is advisable to revisit options for relaxing the stringency of the cash budget. Nevertheless, the revenue to gross domestic product (GDP) ratio, fell marginally to 12.1 percent in FY02, but is projected to reach 12.5 percent in FY03, therefore, with respect to new tax policy measures, it will be important to pay attention to the impact of such measures on poverty and growth. However, given that foreign assistance increased in FY02 to 5.9 percent of GDP, and is projected to increase to 7.9 percent in FY03, there is the need to pursue policies that would support Tanzania's international competitiveness, and minimize the potential "Dutch disease" effects of aid. Upon review of the micro-aspects of development assistance, it would be useful to improve the scope of the information, and in turn, the Ministry of Finance ( MoF) should routinely obtain this information, so as to incorporate/synchronize it with current aid flow data bases. Further recommendations address functional allocation of resources and distribution, requirements concerning auditing, and reporting standards, and, the inclusion of participatory monitoring and evaluation, as an important feedback mechanism into the PER process.